[ATTACH=full]997[/ATTACH]

log(b,((sqrt(3)+sqrt(2))/(sqrt(3)-sqrt(2)))=2log(b(sqrt(3)+sqrt(2)) log(b,((sqrt(3)+sqrt(2))/(sqrt(3)-sqrt(2))) =>(sqrt(3)+sqrt(2))/(sqrt(3)-sqrt(2))........rationalize, multiply (sqrt(3)+sqrt(2)) =((sqrt(3)+sqrt(2))((sqrt(3)+sqrt(2))))/((sqrt(3) - sqrt(2))(sqrt(3)+sqrt(2))) =(((sqrt(3)+sqrt(2))^2)/((sqrt(3) )^2- (sqrt(2))^2)) =((sqrt(3)+sqrt(2))^2)/(3- 2) =((sqrt(3)+sqrt(2))^2)/1 =(sqrt(3)+sqrt(2))^2 then log(b,(sqrt(3)+sqrt(2))^2 =2log(b,(sqrt(3)+sqrt(2))->proven

Is it possible for you to use LaTex or write your reply on paper and then upload here for easy reading?

1. Is this LaTex? 2. If not LaTex, what app did you use to type this reply? 3. Reply using this style of writing from now on. It's a lot easier to read and understand.